PREVALENCE OF NECK PAIN AMONG PHSICAL THERPY STUDENTS IN PESHAWAR - Ali, Muhammad Nayab; Ibrahim, Muhammad (Annals of Allied Health Sciences, 2017)
Objective of the Study: The objective of current study was to report find out prevalence of neck pain among physical therapy students. Subjects & methods: A study was conducted among Physical Therapy students. Standardized Nordic Questionnaire (SNQ) with some modification due to different cultural and social aspects was used for data collection. Questionnaires were distributed among 200 Physical Therapy students. Statistical Package for Social Sciences (SPSS) version 16.0 was used to analyze the data. Results: The prevalence of Neck Pain among the physical therapy students in Peshawar was 84%. There were 40% Male and 60% Female students. Majority of students having neck pain were in age group of 20-30 years whereas 28% students reported to have neck pain belonged to Final Year. Effects of neck pain on ADL such as sleeping disturbances were reported among 23.3% students, Difficulty using lapotop in 16.5%, difficulty using computer in 14.5%, driving difficulties in 17% students were reported. Overall disability rate among these students was mild (65.5%). Conclusion: The Prevalence of neck pain among the Physiotherapy students is found out to be very high with certain risk factors contributing to it. Also females were found to have more neck pain ratio then the male students